Resensi Buku: Incarnate Earth: Deep Incarnation and the Face of Christ - Sendjaja, Hendri Mulyana (Faculty of Theology Duta Wacana Christian University, 2024)
Conversations about Christ or Christology are increasingly alive with the times. Many Christian theologians rethink what kind of Christology and how it can relate to and be creative for the changing context of the times. One of them is Matthew Eaton, who, through his book Incarnate Earth: Deep Incarnation and the Face of Christ, promotes a new, non-anthropocentric model of Christology, which seeks to connect with the context of the lives of the inhabitants of the Earth in facing various challenges in environmental crises.